Binary logistic regression analysis of instructional leadership factors affecting English language literacy in primary schools - Sio, Jarrod Jyh Lih; Ramlee Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper discusses the factors contributing to student achievement in English language literacy in primary schools within Sibu division, Sarawak, Malaysia. The study involved 694 teachers who taught in 105 lower primary schools. Binary logistic regression was applied to predict the instructional leadership’s influence on student achievement in literacy. The findings revealed that one dimension of instructional leadership - supervising and evaluating instruction - emerged as strong predictors of literacy. The result indicated that schools were more than 17 times more likely to achieve 100% literacy rate when the instruction processes were supervised and evaluated by the headmasters. Supervision and evaluation of instruction had a positive influence on students’ achievement for English language literacy, hence making this a possible course of action for school heads. More comprehensive studies are needed to ascertain its consistency as well as investigating other predictors for literacy.